2017
DOI: 10.1093/mnras/stx795
|View full text |Cite
|
Sign up to set email alerts
|

The infrared to X-ray correlation spectra of unobscured type 1 active galactic nuclei

Abstract: Citation for published item:qr¡ %EferneteD sF nd mos elmeidD gF nd vndtD rF nd rdD wF tF nd flokovi¡ D wF nd eostEulidoD tF eF @PHIUA 9he infrred to Ery orreltion spetr of unosured type I tive glti nuleiF9D wonthly noties of the oyl estronomil oietyFD RTW @IAF ppF IIHEIPTF Further information on publisher's website: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 104 publications
(129 reference statements)
1
10
0
Order By: Relevance
“…Groves, Dopita & Sutherland 2006). However, a recent study reported that [Ne II] emission line can be significantly contaminated by the AGN-dominated systems using a sample of unobscured type 1 AGN (García-Bernete et al 2017). Because of that, and as a sanity check, we also employ other ionization ratios involving emission lines such as [O IV] and [Ar II] (see Appendix C).…”
Section: Dust Components and The Hardness Of The Radiation Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Groves, Dopita & Sutherland 2006). However, a recent study reported that [Ne II] emission line can be significantly contaminated by the AGN-dominated systems using a sample of unobscured type 1 AGN (García-Bernete et al 2017). Because of that, and as a sanity check, we also employ other ionization ratios involving emission lines such as [O IV] and [Ar II] (see Appendix C).…”
Section: Dust Components and The Hardness Of The Radiation Fieldmentioning
confidence: 99%
“…Spinoglio, Andreani & Malkan 2002;Ho & Keto 2007;Pereira-Santaella et al 2010). However, this emission line could be significantly contaminated by the AGN (García-Bernete et al 2017). These SFR indicators are mainly important in the vicinity of AGN-dominated systems where classical SF indicators normally fail.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulties in decomposition of the narrow Hα, Hβ and [NII] lines in the initial sample of Type 1 AGNs, to check some relations between narrow lines, we also consider a sample of Type 2 AGNs, taken from the literature (more in Section 4.4). The sample is taken from Hernán-Caballero et al (2015) and García-Bernete et al (2016), as these authors performed the fitting of CASSIS spectra of ∼150 objects -Seyfert 2 galaxies, LINERs and HII regions, using deblendIRS routine (we use the same routine in this work). We took the fitting results that they obtained (spectral index, α and fractional contributions of AGN and PAH in the spectra -RAGN and RPAH, respectively) for all objects for which we found the log([OIII]/Hβ) and log([NII]/Hα) measurements in the other literature.…”
Section: The Sample Of Type 2 Agns From the Literaturementioning
confidence: 99%
“…To confirm these doubts, taking into account that it is complicated to decompose the narrow lines in the Type 1 AGNs (see the Appendix A and Popović & Kovačević 2011), we chose a sample of Type 2 AGNs (see Table 2 and Section 2.2). We made another BPT diagram, composed from the various LINER, HII regions and Seyfert 2 galaxies, from the samples of Hernán-Caballero et al (2015) and García-Bernete et al (2016). That BPT diagram is shown in the Fig.…”
Section: Comparison Between Starburst Fraction At Optical (Bpt Diagra...mentioning
confidence: 99%
“…It is well-known that active galactic nuclei (AGNs) show a positive "linear" correlation between the mid-infrared (IR) and the hard X-ray luminosity in a log-log space (e.g., Lutz et al 2004;Horst et al 2008;Fiore et al 2009;Gandhi et al 2009;Ichikawa et al 2012;Matsuta et al 2012;Asmus et al 2015;Mateos et al 2015;Isobe et al 2016;García-Bernete et al 2017;Ichikawa et al 2017). In the context of the AGN unified model (e.g., Antonucci 1993;Urry & Padovani 1995), the X-ray emission in an AGN is generated in a hot corona by inverse Comp-⋆ E-mail: toba@kusastro.kyoto-u.ac.jp ton scattering of thermal photons from an accretion disk (e.g., Sunyaev & Titarchuk 1980;Haardt & Maraschi 1991, 1993.…”
Section: Introductionmentioning
confidence: 99%